Aspirin with or without statin in the treatment of endotheliitis, thrombosis, and ischemia in coronavirus disease - Florêncio,Francisco Kleyton Zacarias (2020)
Abstract INTRODUCTION: In the genesis of coronavirus disease (COVID-19), there is a process of endotheliitis associated with thrombotic changes, no studies have reported the use of acetylsalicylic acid (ASA) as a possible therapeutic approach. Statins could potentiate the ASA therapy. METHODS: This is a series of 14 cases with a laboratory-confirmed diagnosis of COVID-19. All patients underwent the ASA therapy. Those who had risk factors for vascular disease also underwent the high-potency statin therapy. When symptoms were totally or practically resolved, patients were discharged and advised to continue medications for a complementary time, according to the clinical evolution of each patient. RESULTS: The mean age of monitored patients was 48.6 years. A total of 78.6% patients presented with at least one comorbidity, which could have contributed as a risk factor for a poor prognosis in the evolution of COVID-19. Four patients had secondary bacterial infections; three patients needed hospitalization. None of the cases progress to stage III, and all patients had remission of symptoms, with 100% survival. CONCLUSIONS: the process of endothelial dysfunction in COVID-19 involves disseminated thrombosis, initially microvascular and later expansion into larger vessels. ASA could act as a secondary prophylaxis and prevent thrombosis from developing and reaching stage III of the disease. As this was a case series, we cannot provide definitive conclusions; however, this study allows us to formulate hypotheses and support clinical trials to evaluate benefits of the ASA therapy in the treatment of COVID-19.